Application of microwave technology for home industry - Khamis, N.H H; Ramli, S; Ean, T.C; Bakar, W.Z.A.W (2005)
Conventional methods have been used to dehydrated fruits and vegetables for the purpose of preservation and to extend the storage life of flowers, fruits and vegetables. However, these conventional methods have low drying efficiency, long drying time and the quality of the dried flowers, fruits and vegetable are rather poor. The application of microwave in flowers, fruits and vegetables dehydration is studied to verify the effectiveness of microwave dehydration, and to maintain the quality of dried flowers, fruits and vegetables as compared to conventional methods. Microwave dehydration provides volumetric heating effect where heat is generated within the product itself and heats the entire volume at a faster rate. The parameters to be controlled during microwave dehydration had been identified to give better quality output, higher drying efficiency and shorter drying time. A simple microwave dehydration system had been build to understand better the architecture of microwave dehydration system. Microwave dehydration had decreased the dehydration time of flowers, fruits and vegetables with higher energy and drying efficiency. In this study, the microwave dehydration process was able to dry flowers that have better color and texture. It was also able to dry the moisture content of carrot that is 4 to 8 times faster than hot air dehydration. This study has shown the potential of the application of microwave technology for the benefit of home industry.